ANALISIS PENGUKURAN KINERJA DENGAN PENDEKATAN BALANCED SCORECARD PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA DHARMA KOTA BENGKULU - Ertika Nadila Sari; Halimatusyadiah (JURNAL FAIRNESS, 2022)
In the face of an increasingly complex business environment such as the current performance measurement methods are needed to assess the company's performance accurately and thoroughly. In this case the method to be used is the Balanced Scorecard. Intended use of the Balanced Scorecard method is to measure the performance of companies from four Perspektif, namely: financial perspective, customer perspective, growth/ learning, internal business perspective. The objective of this research is to find out of financial performance of PDAM of Bengkulu City. Measuring the financial performance was used balanced scorecard. The author conducted measurements on PDAM Bengkulu using data years 2014-2017 to analyze the financial perspective, while for other perspectives using company data and calculation of a questionnaire distributed to employees and customers PDAM PDAM Bengkulu Bengkulu City. The results of measurements that have been made known that the performance assessment PDAM Bengkulu city as a whole good enough for the perspective of growth / learning, and internal business perspective and results for the customer's perspective was quite satisfied for services offered PDAM Bengkulu, the assessment results financial perspective PDAM Bengkulu figures are still categorized low. The conclusion that can be drawn through the analysis that has been done is that the Balanced Scorecard is a good method for measuring the performance of the company, because the Balanced Scorecard raised important aspects are overlooked by traditional performance measurement.